1993
DOI: 10.1093/chemse/18.1.27
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between sweet taste and seasonal body weight changes in a primate (Microcebus murinus)

Abstract: Abstract.The relationship between obesity and taste, especially sweet taste, has been and is of interest. From this point of view of a small primate, the lesser mouse lemur (Microcebus murinus), is of particular interest. It goes through a yearly cycle of physiological changes, one of which is an extreme variation in body weight of up to 100%. This occurs concomitantly with significant changes of the animal's liking for sucrose; measured by two-bottle preference tests, the threshold for sucrose changes from 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…Overall preference tests are in good agreement with evoked potentials recorded from the chorda tympani [11,12,24,27], demonstrating that species of the genera Eulemur, Saimiri and Macaca are able to taste lower concentrations of sucrose (10-30 mM) than the smaller species of the genera Microcebus and Saguinus (30-70 mM). A simple causal explanation for such relationships would be that, if tongue surface is positively related to body weight, the recruitment of a greater number of taste buds as body weight increases is sufficient to elicit a more intense signal.…”
Section: Resultssupporting
confidence: 58%
“…Overall preference tests are in good agreement with evoked potentials recorded from the chorda tympani [11,12,24,27], demonstrating that species of the genera Eulemur, Saimiri and Macaca are able to taste lower concentrations of sucrose (10-30 mM) than the smaller species of the genera Microcebus and Saguinus (30-70 mM). A simple causal explanation for such relationships would be that, if tongue surface is positively related to body weight, the recruitment of a greater number of taste buds as body weight increases is sufficient to elicit a more intense signal.…”
Section: Resultssupporting
confidence: 58%
“…It is surpris ing that a very high taste threshold for fruc tose was found (100-119 mM ), whereas a re sponse of the chorda tympani was recorded for sucrose concentrations as low as 10 mM in this species [16]. Further data are needed to determine whether such a difference reflects an actual differential sensitivity towards sug ars or merely reflects the atypical response of a single individual.…”
Section: Discussionmentioning
confidence: 81%
“…On the one hand, there is evidence based on investi gations of three primate species [10,11] that both the two-bottle test and the electrophysiological recording of the evoked firing activity of the chorda tympani nerve yield similar taste thresholds for sucrose. On the other hand, it has been demonstrated that the 'be havioural threshold' for sucrose of Microcebus murinus (Cheirogaleidae) varies seasonal ly, with no concomitant change in the re sponse of peripheral nerves [8,12]. Accord ingly, the possibility that taste thresholds for fructose of lemurs mainly reflect motivational aspects of feeding behaviour, as in M. murinus, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the interindividual variability found in humans spans a range from 0.125 to 0.5 for the JND for sucrose [8], and although the animals here showed very little interindividual difference in performance, factors such as nutritional state [10] and seasonality of physiological pa rameters [11] may influence gustatory sensi tivity in primates. Secondly, while the JND for humans has been established using sophis ticated signal detection methods, the two-bot tle preference test provides only a conserva tive approximation of a species' limits of gus tatory capacity.…”
Section: Discussionmentioning
confidence: 69%